3D-printed flexible flow-field plates for bendable polymer electrolyte membrane fuel cells - Yoo, Hongnyoung; Kwon, Obeen; Kim, Jaeyeon; Cha, Hyeonjin; Kim, Hyeok; Choi, Heesoo; Jeong, Seokhun; Lee, Young Jo; Kim, Baekhyeom; Jang, Gye Eun; Koh, Je Sung; Cho, Gu Young; et al. (Journal of Power Sources, 2022)
3D-printed flexible flow-field plates are employed in this study to realize a bendable polymer electrolyte membrane fuel cell (PEMFC). The prepared bendable PEMFC consists of a membrane electrode assembly (MEA), current collectors, and flow-field plates. The performance of the fuel cell is measured in the flat and bent positions. Polarization curves and impedance plots are analyzed to assess the fuel cell performance. A peak power density of 87.1 mW cm−2 is obtained for the fuel cell with the maximum bending, while a power density of 30.2 mW cm−2 is obtained in the flat position. The enhanced performance is attributed to the compressive stress applied to the reaction sites of the MEA during bending of the fuel cell. The compressive stress is calculated using finite element analysis (FEA). According to the FEA results, the compressive stress occurring at the MEA intensifies as the curvature of the fuel cell increases, resulting in significantly decreased ohmic and charge transfer resistances. The successfully realized bendable fuel cell with 3D-printed flexible flow-field plates exhibits flexibility, decent performance, and a simple structure. It is also competitive in terms of the cost of manufacturing owing to the use of 3D printing.
Keywords: 3d-printed flow-field plate; Bendable fuel cell; Current flows; Current-collector; Finite element analyse; Flexible flow; Flow-field plate; Interfacial contact resistance; Membrane electrode assemblies; Performance; 3D-printed flow-field plate; Bendable fuel cell; Compressive stress; Finite element analysis; Interfacial contact resistance; Polymer electrolyte membrane fuel cell